Equivalent Energy Design Procedure for Earthquake Resilient Fused Structures. Issue 2 (May 2018) - Yang, T. Y.; Tung, Dorian P.; Li, Yuanjie
It has been observed in recent earthquakes worldwide that even countries with modern building codes suffer significant structural damages because earthquake energy is dissipated through inelastic deformation of structural components. Unrecoverable damages and prolonged downtime can be minimized using earthquake resilient structures, where earthquake energy is dissipated using specially designed and detailed structural fuses. Fuses are decoupled from gravity system and can be replaced efficiently. Earthquake-resilient fused structures cannot be routinely designed unless there is a simple design procedure. This paper presents an equivalent energy design procedure (EEDP) for the seismic design of fused structures. EEDP allows designers to select different performance objectives at different earthquake shaking intensities. EEDP also allows engineers to select structural members to achieve the desired structural period, strength, and deformation with simple hand calculations without iterations. This practical and efficient design procedure is illustrated via an earthquake resilient fused truss moment frame (FTMF). The nonlinear dynamic analysis result shows that the prototype FTMF can have controlled failure mechanism and drifts selected by the engineer at multiple earthquake shaking intensities.